Work-related stress and bullying: gender differences and forensic medicine issues in the diagnostic procedure - Tonini, Stefano (BioMed Central, 2011)
BACKGROUND: The attention of international agencies and scientific community on bullying and work-related stress is increasing. This study describes the gender differences found in victims of bullying and work-related stress in an Italian case series and analyzes the critical issues in the diagnostic workup. METHODS: Between 2001 and 2009 we examined 345 outpatients (148 males, 197 females; mean age: 41 ± 10.49) for suspected psychopathological work-related problems. Diagnosis of bullying was established using international criteria (ICD-10 and DSM-IV). RESULTS: After interdisciplinary diagnostic evaluation (Occupational Medicine Unit, Psychology and Psychiatry Service), the diagnosis of bullying was formulated in 35 subjects, 12 males and 23 females (2 cases of Post-Traumatic Stress Disorder and 33 of Adjustment Disorder). Fifty-four (20 males, 34 females) suffered from work-related anxiety, while work-unrelated Adjustment Disorder and other psychiatric disorders were diagnosed in 7 and 112 subjects, respectively. Women between 34 and 45 years showed a high prevalence (65%) of "mobbing syndrome" or other work-related stress disorders. CONCLUSIONS: At work, women are more subject to harassment (for personal aspects related to emotional and relational factors) than men. The knowledge of the phenomenon is an essential requisite to contrast bullying; prevention can be carried out only through effective information and training of workers and employers, who have the legal obligation to preserve the integrity of the mental and physical status of their employees during work.